Semiotika Visual Logo Bumbu Bamboe dan Perannya Sebagai Identitas Perusahaan - Restiawan Permana; Yusmawati (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
The use of logos is often associated with the company's strategy in conveying its business message. Through logos, companies can form an image, identity, and understanding of the community. Logos are generally used by companies as an identity to distinguish them from other companies. The logo is a form of representation of the company's vision and mission that has signs in it. This sign consists of several visual elements, such as line, shape, space, and color. In order to be able to analyze the sign system and the meaning contained in the logo, we need a method so that the meaning contained behind the symbol can be understood. This method is called semiotics. In this study, researchers examined the Bumbu Bamboe logo using a qualitative approach and Charles Sanders Peirce's semiotic method. Pierce distinguishes the relationship between signs and their references into three types of relations, namely: icons, indexes, and symbols. The signs that the author analyzed are pictures of stems and leaves, the words “bamboe”, the words “Since 1968”, and the words “Authentic Recipes”. The role of the Bumbu Bamboe logo is as a corporate identity that describes the company's vision, mission, and goals.